A Combined Model of Lean Manufacturing Tools to Increase Efficiency in a Peruvian Textile Company - Condeso Carrizales, Kevin Orlando (2022)
In Peru, there are more than 9,000 micro-enterprises focused on the production of garment. Over the last few years, these numbers have remained stable while the number of medium-sized and large companies dedicated to this sector has decreased considerably. This situation is partly attributable to the current situation in the country due to the global pandemic, as well as the low-operational performance of the companies in this sector. However, just as this situation has left a large part of the economy paralyzed, the economic reactivation stimulated by the government represents a great opportunity to re-enter into the textile industry. Consequently, this paper proposes a model to improve the competitiveness of a case belonging to this sector through a model for improving the overall efficiency of the production process of its standard product based on tools oriented to the Lean Manufacturing philosophy, so that by reducing errors and shortening unproductive times, the productivity and competitiveness of the case study is increased. This model aims to focus on error reduction to improve its competitiveness, through a low-cost implementation that can be applied in almost any small manufacturing company. In order to validate this model, a pilot test was carried out using SMED, Poka-Yoke and work standardization tools, which resulted in a 20% reduction in recurring processes and a 21% reduction in set-up times, achieving a production efficiency of 84%.